JUSTIFICATION OF THE DISTANCE BETWEEN SHORT TOPS ON THE WORKING HORIZONS OF THE MINE WHEN USING LOADING AND DELIVERY MACHINES - Khakimov, Shadiboy Ikmatullayevich; Qobilov, Olimjon Sirojovich; Abruyev, Samandar Shodmon o‘g‘li (Innovative Development in Educational Activities, 2023)
To the article the worked out is driven on the basis ofresearches, methodology of choice of optimal distancebetween crossheadings in mine horizon at development ofhigh-dipping tendon deposits of different power with the useof self-propelled technique and offered graphic results forengineering calculations.